Rainfall interception and nutrient flux in rubber plantation - Metia, Shankar; George, Sherin (Journal of Plantation Crops, 2009)
Matured rubber plantation partitioned 80.5, 8.5 and 11 per cent of total rainfall as through fall, stem flow and interception, respectively. Interception and trunk storage capacity of rubber was 0.8 and 1.0 mm, respectively. Maximum litter interception was 0.9 mm and annual litter interception estimated as 15.0 mm. Acidity of rainwater reduced after passing through rubber foliage, whereas, that of stem flow did not, indicating the role of foliage in reducing the acidity. Gross nutrient addition through rainfall was 45.2, 13.2, 23.8, 4.7, 0.6, 0.5 and 0.6 kg N, K, Ca, Mg, Fe, Cu and Zn/ha, respectively, Similarly rubber canopy also enriched nutrients except N. Nutrient leachability from rubber canopy was in the order of Ca>K>Cu>Mg>Fe. Throughfall N content was lower than rainwater indicating absorption by foliage. Nutrient addition through rainfall process was to the extent of 30-50 per cent of that supplied through leaf litter, indicating the importance of rainfall process in cycling of nutrient in ecosystem.